AMPK Contributes to Cardioprotective Effects of Pterostilbene Against Myocardial Ischemia- Reperfusion Injury in Diabetic Rats by Suppressing Cardiac Oxidative Stress and Apoptosis - Kosuru, Ramoji; Cai, Yin; Kandula, Vidya; Yan, Dan; Wang, Chunyan; Zheng, Hong; Li, Yalan; Irwin, Michael G.; Singh, Sanjay; Xia, Zhengyuan (Cellular physiology and biochemistry, 2018)
Background/Aims: Pterostilbene (PT) exerts antidiabetic effects by decreasing blood glucose and modulating lipid metabolism and has been shown to attenuate myocardial ischemia-reperfusion (IR) injury in non-diabetic subjects. However, whether PT can protect against myocardial IR injury in diabetes is unknown. AMPK stimulation is indispensable in offering cardioprotection against myocardial IR injury in diabetes by limiting cardiac apoptosis. Thus, we hypothesized that PT may confer protection against myocardial IR injury in diabetes via AMPK activation. Methods: Sprague-Dawley rats at eight weeks of diabetes induction (induced by an intravenous dose of 65 mg/kg streptozotocin) were administered with vehicle or PT (20 and 40 mg/kg/day, p.o.) for four weeks (starting from week 9 to 12). At the end of week 12, myocardial IR injury was induced by subjecting the diabetic rats to 30 minutes of coronary artery ligation and followed by 2 hours of reperfusion. In in vitro studies, rat primary cardiomyocytes were incubated with low glucose (LG, 5.5 mM) or high glucose (HG, 30 mM) and exposed to 45 minutes hypoxia and 2 hours reoxygenation in the presence or absence of PT (0.5 µM) or the AMPK inhibitor compound C (CC, 5 µM). Results: PT significantly reduced post-ischemic cardiac infarct size, oxidative stress, plasma lactate dehydrogenase (LDH), creatine kinase-MB levels and apoptosis in diabetic rats. In cardiomyocytes, PT decreased hypoxia/ reoxygenation-induced oxidative stress, attenuated LDH and cleaved caspase3/caspase3 ratio and increased Bcl-2/Bax ratio and AMPK phosphorylation. However, CC administration blunted the cardioprotective effects of PT both in vivo and in vitro. Conclusion: Suppressing cardiac oxidative stress and apoptosis via AMPK stimulation may represent a primary mechanism whereby pterostilbene attenuates diabetic myocardial IR injury.